PENGARUH PROMOSI PENJUALAN DAN INOVASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN DAN DAMPAKNYA TERHADAP LOYALITAS PELANGGAN - Eko Boedhi Santoso; Joko Samboro (Adbis: Jurnal Administrasi dan Bisnis, 2017)
The main objective of this study is: a) identify and analyze to Sales Promotion and Product Innovation Effect on Costumers Buying Decision and b). To find and analyze Sales Promotion and Product Innovation Effect on the Decision of Costumers Loyalty Purchasing through Gedang Ganteng. Location Mayjen Panjaitan Malang. while the sample amounted to 100 costumers which is the minimum threshold for path analysis. The results of this study indicate that: questionnaires were used valid and reliable, sweet model used for predection good and getting better service sales promotion innovation product services, the higher the stronger loyalty through costumer purchase decision as well as the influence of the total variables studied amount 65% Key words: sales promotion, innovation of product, decisions making and loyalty.